Pengaruh Keberagaman Gender terhadap Kinerja Perusahaan dengan Corporate Sosial Responsibility sebagai Variabel Mediasi - Meysa Fanesha; Nurzi Sebrina (Jurnal Eksplorasi Akuntansi, 2024)
This study aims to analyze the effect of gender diversity on firm performance with corporate social responsibility as an intervening variable. Gender diversity is measured by the ratio of the presence of women on the board of directors and commissioners to the total number of members of the board of directors and commissioners. Firm performance is assessed using three proxies: Return on Assets (ROA), Return on Equity (ROE), and Tobin's Q. CSR is evaluated using the CSR disclosure index, which Garanina and Kim developed in 2023. The data used are annual reports and sustainability reports of consumer non-cyclicals companies listed on the Indonesia Stock Exchange from 2018-2022. Consumer non-cyclicals companies produce goods or services to meet primary needs. Samples were taken using purposive sampling, totaling 64 companies. The analysis used the Partial Least Square (PLS) method. The results show that gender diversity does not affect firm performance with ROA and ROE proxies but does affect performance with the Tobin's Q proxy. Additionally, gender diversity negatively affects CSR, and CSR has a significant positive effect on performance with the ROA proxy but no effect on ROE and Tobin's Q proxies. CSR mediates the effect of gender diversity on firm performance with the ROA proxy but does not mediate the effect on performance with the ROE and Tobin's Q proxies.